2001
DOI: 10.1207/153248301753225919
|View full text |Cite
|
Sign up to set email alerts
|

Power Use in Cooperative and Competitive Settings

Abstract: In this study we argue that when powerholder and target operate in a cooperative context, the decision to use power is influenced by the motive to reach positive joint outcomes. When the context is competitive, the use of power is more dictated by the desire to gain positive outcomes at the expense of the target. Therefore, factors that are indicative of how to bring about positive outcomes for the target will only influence power use in a cooperative context. The results of an experimental study with a 2 (soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Fitting‐in is essential. Other research has shown that the combination of a cooperative culture and the use of power can lead to desirable behaviors (Knippenberg, Knippenberg, and Wilke 2001). Knippenberg et al's study revealed that the use of power in a cooperative environment (versus a competitive environment) “is more likely to be instigated by the desire to help the other in attempts to reach certain goals” (2001, 297).…”
Section: Summary Of Overall Findingsmentioning
confidence: 99%
“…Fitting‐in is essential. Other research has shown that the combination of a cooperative culture and the use of power can lead to desirable behaviors (Knippenberg, Knippenberg, and Wilke 2001). Knippenberg et al's study revealed that the use of power in a cooperative environment (versus a competitive environment) “is more likely to be instigated by the desire to help the other in attempts to reach certain goals” (2001, 297).…”
Section: Summary Of Overall Findingsmentioning
confidence: 99%